2023
DOI: 10.5194/essd-15-447-2023
|View full text |Cite
|
Sign up to set email alerts
|

Multi-hazard susceptibility mapping of cryospheric hazards in a high-Arctic environment: Svalbard Archipelago

Abstract: Abstract. The Svalbard Archipelago represents the northernmost place on Earth where cryospheric hazards, such as thaw slumps (TSs) and thermo-erosion gullies (TEGs) could take place and rapidly develop under the influence of climatic variations. Svalbard permafrost is specifically sensitive to rapidly occurring warming, and therefore, a deeper understanding of TSs and TEGs is necessary to understand and foresee the dynamics behind local cryospheric hazards' occurrences and their global implications. We present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Nicu, Lombardo, et al, 2021 presented a preliminary view on thaw slumps affecting cultural heritage in Nordenskiöld Land, Svalbard, concluding (based on data from 2009 to 2011) that thaw slumps are affecting eight sites (represented by a trapping cabin, restored grave, and new Russian cross—they are taken as one, remains of posts, Russian hut, a house foundation, a boat house, a cabin, and a Russian cottage). Making predictive models of climate‐induced processes (especially thaw slump), will lead to a better understanding of the environmental factors contributing to their occurrence and development (Nicu et al, 2022). Models made for certain areas could be adapted for other circum‐Arctic areas (Rudy et al, 2016), as is a frequent practice for landslides in non‐Arctic and non‐Antarctic areas.…”
Section: Impacts Of Climate Change On Immovable Cultural Heritage In ...mentioning
confidence: 99%
“…Nicu, Lombardo, et al, 2021 presented a preliminary view on thaw slumps affecting cultural heritage in Nordenskiöld Land, Svalbard, concluding (based on data from 2009 to 2011) that thaw slumps are affecting eight sites (represented by a trapping cabin, restored grave, and new Russian cross—they are taken as one, remains of posts, Russian hut, a house foundation, a boat house, a cabin, and a Russian cottage). Making predictive models of climate‐induced processes (especially thaw slump), will lead to a better understanding of the environmental factors contributing to their occurrence and development (Nicu et al, 2022). Models made for certain areas could be adapted for other circum‐Arctic areas (Rudy et al, 2016), as is a frequent practice for landslides in non‐Arctic and non‐Antarctic areas.…”
Section: Impacts Of Climate Change On Immovable Cultural Heritage In ...mentioning
confidence: 99%
“…Satellite imagery at 30 m resolution from Landsat has been used to analyze RTSs and thermokarst lakes in the region of Alaska within the circumpolar Arctic, eastern Canada, and Siberia (Nitze et al, 2018). Nicu et al (2023) employed orthorectified imagery with a resolution of 5 m to visually interpret and identify cryospheric hazards (such as thaw slumps and thermo-erosion gullies) in Nordenskiöld Land, covering an approximate area of 4000 km 2 in the Svalbard Archipelago. The permafrost zone of the Qinghai-Tibetan Plateau (QTP) has been a site of thermokarst geomorphology research in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…To complement this assessment, we also report the probability density function of the susceptibility spectrum, together with the estimated Youden Index (Y = 0.52) in Figure4b. This cutoff leads to the confusion matrix and confusion maps (see also,Nicu et al, 2023) shown in Figure4c. There, we summarize the frequency distribution for each class of the confusion matrix and plot the corresponding geographic distribution expression across China.…”
mentioning
confidence: 99%